Efektifitas Model Kooperatif Team Games Tournament (TGT) Terhadap Hasil Belajar Siswa Dalam Pembelajaran Pendidikan Jasmani, Olahraga Dan Kesehatan - Abdul Hafid; Heryanto Nur Muhammad; Setiyo Hartoto (Jurnal Porkes, 2026)
Physical Education, Sports, and Health (PJOK) learning at the elementary school level still faces challenges in the form of low student engagement and a lack of innovation in learning models. This study aims to test the effectiveness of the Team Games Tournament (TGT) cooperative model on improving the PJOK learning outcomes of fifth-grade students at SDN Gedong 10, East Jakarta. The study used a quantitative approach with a one-group pretest-posttest design. The sample consisted of 31 students selected through purposive sampling. The assessment instruments covered three areas of learning outcomes: cognitive (multiple-choice tests), psychomotor (performance tests), and affective (attitude observations). The data were analyzed using a paired t-test and Cohen's d effect size. The results showed a significant increase in learning outcomes after the implementation of the TGT model, with a pretest average of 83.71 and a posttest average of 87.84 (p = 0.000; effect size 0.939, large category). The highest increase occurred in the cognitive domain (difference of 5.16; effect size 0.87), followed by psychomotor (difference of 4.26; effect size 0.81), and affective (difference of 2.97; effect size 0.64). The conclusion of this study is that the TGT cooperative model has been proven effective in comprehensively improving PJOK learning outcomes and creating active, enjoyable, and student-centered learning.